Peran Pramuka dalam Menanamkan Karakter Islami pada Siswa - Musyarofah, Atiqatul; Rahman, Ahmad Jayyid Jawadur; Muftiyah, Al; Masruroh, Fitriatul (INCARE, International Journal of Educational Resources, 2025)
This study aims to explain that Scouting (Pramuka) can serve as an effective medium for instilling Islamic character values in fourth-grade students at Gontor Banyuwangi. This is deemed essential in shaping strong personalities with noble character. One of the instruments utilized in character development is Scouting activities. Scouting functions as a means to cultivate Islamic values, discipline, solidarity, and social awareness, which are reflected in its various activities. The researcher employed a qualitative research approach, specifically descriptive qualitative research, with the aim of describing and analyzing phenomena, attitudes, and the thoughts of individuals or groups through qualitative descriptive patterns. In collecting the data, three primary techniques were used: observation, interviews, and documentation. Data analysis involved three stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate that Scouting activities at Gontor Banyuwangi have effectively enhanced students’ understanding of Islamic teachings, while also strengthening moral and social values in their daily lives. Consequently, Scouting has become one of the key components in the formation of Islamic character among students within the pesantren educational environment. The study concludes that Scouting can be utilized as an effective tool in shaping a solid Islamic character in students at Islamic boarding schools (pesantren).